Instabilitas tokoh-tokoh bissu dalam fiksi Faisal Oddang: Fenomena zona intertekstualitas heterotopia - Hariyono, Saharul (citeus, 2020)
This article describes the phenomenon of instability bissu characters in literary works by Faisal Oddang. The research subjects were the novel Tiba Sebelum Berangkat and short story anthology Sawerigading Datang dari Laut. Both of these works were used as a source of primary data, whereas books or journal articles about bissu was used as a secondary data source. This article utilizes the theory initiated by Brian McHale statement about literary work in the postmodernist zone. If the dominant is the ontological trait rather than epistemological, it raises issues and components of different and encroaches on the historical zone. The analysis was shown from fiction to fiction, such as one written by Oddang about bissu character which was presented in inconsistent and encroaching way. Oddang presented bissu in various characterizations and professions. A bissu was shown in one story to have a libido, to work as a spy for the rebellious act, and that the leader bissu only prioritizes ego. In the other story, however, a bissu was shown to work as bridal makeup artist. Still in another story, bissu was shown to work as a translator for the epic I La Galigo. Inconsistency is also seen at the characters of Isuri and Rahing, whom he often utilized in the storyline. The changes of bissu characters in every literary work showed an ontological instability—a universe called intertextuality zone heterotopia. Therefore, Oddang’s works belong to postmodernism, giving insights to readers that there is a new subject being painted.